UMA ANÁLISE DA ABORDAGEM GRAMATICAL DE UM LIVRO DIDÁTICO DE LÍNGUA PORTUGUESA - SILVA, MATHEUS SANTOS DA (2020)
The focus of this work is on the analysis of the approach of the linguistic-grammatical contents of a Textbook. Our main objective was to analyze the activities of unit three, which deals with morphosytactic contents. For this study, we initially researched works that deal with Applied Linguistics and teaching practice via Linguistic Analysis, such as in Mendonça (2006), Travaglia (2002) and Neves (2003) to support our research. Then we have exposed and discussed how language teaching should be carried out in the final years of elementary school, based on the National Curriculum Parameters (1998) in the National Common Curriculum Base (2018), as well as in the National Plan of Book and Didactic Material. After that, we set out to analyze the unit mentioned above in the LD and realize that there is still much to be done about the grammatical approach in this didactic material, since the use of the text as a pretext and a metalinguistic approach are still present in linguistic-grammatical activities.